Fangchinoline attenuates hepatic fibrosis by regulating taurine metabolism and oxidative stress - Hui Yin; Hui Yin; Hang Lian; Yawen Wang; Luoting Chen; Xueting Liu; Yange Liu (Frontiers in Pharmacology)
BackgroundHepatic fibrosis emerges as a pathological hallmark in the pathogenesis of chronic hepatopathies. Stephania tetrandra S. Moore is a traditional Chinese herb used to treat liver disease. However, the anti-hepatic fibrosis effect of fangchinoline (FAN), an active ingredient of S. tetrandra S. Moore, has not been reported. This study aimed to elucidate the anti-hepatic fibrosis effect of FAN and clarify the underlying molecular mechanisms.MethodsThe DEN-induced hepatic fibrosis mouse model, primary murine hepatic stellate cells (HSCs), and TGF-β-induced activation model of HSCs were used to explore the anti-fibrotic effect of FAN. The proteomics analysis was used to predict the pharmacodynamic mechanisms of FAN, and follow-up validation assays were performed with in vivo and in vitro experiments.ResultsFAN alleviated DEN-induced liver fibrosis in mice, reducing biomarker levels, slowing histopathological changes, and inhibiting collagen deposition. FAN suppressed HSCs activation and the biosynthetic abilities of the extracellular matrix. Proteomics was used to explore the mechanisms of FAN action, which is related to the regulation of taurine metabolism. FAN reversed DEN-induced changes in the levels of taurine and key enzymes that catalyze taurine synthesis. Additional taurine reinforces the regulatory effect of FAN on HSCs activation. Taurine could inhibit oxidative stress. FAN reduced DEN-induced ROS accumulation, which may be associated with Nrf2 pathway activation. Cleaning ROS with N-acetylcysteine enhanced the anti-fibrotic effects of FAN.ConclusionFAN can alleviate hepatic fibrosis by regulating taurine metabolism and oxidative stress, which has an important theoretical value.